A hebraisztikai műfajokban tükröződő szellemi hatások a 17. századi protestáns peregrinusainknál - Koltai, Kornélia (Studia Litteraria, 2026)
This paper explores the Hebrew-oriented scholarly activities of seventeenthcentury Hungarian Protestant peregrini, including Bible translation, grammatical works, and congratulatory poetry (carmina gratulatoria). This study considers how these genres interacted, and their place within the intellectual and ideological context of the period. The study argues that these Hebrew-focused endeavours contributed both to the standardization of the Hungarian language and to the formation of national consciousness.